2011
DOI: 10.1155/2011/638058
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a unique disease with a clinical presentation, epidemiology, and histopathology differing from other squamous cell carcinomas of the head and neck. NPC is an Epstein-Barr virus-associated malignancy with a marked racial and geographic distribution. Specifically, it is highly prevalent in southern China, Southeast Asia, and the Middle East. To date, most NPC patients have been diagnosed in the advanced stage, but the treatment results for advanced NPC are not satisfactory. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 65 publications
1
74
0
5
Order By: Relevance
“…The treatment also depends on the results of the pathologist´s report, especially after determining the stage of cancer in the patient's body 1 . Furthermore, the greatest benefits provided by histopathological examination is determined of the classification scheme of cancer, which depend on the tumors gross morphology, the degree of cellular differentiation and the tumor´s histogenic or cytogenic origin 1,27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment also depends on the results of the pathologist´s report, especially after determining the stage of cancer in the patient's body 1 . Furthermore, the greatest benefits provided by histopathological examination is determined of the classification scheme of cancer, which depend on the tumors gross morphology, the degree of cellular differentiation and the tumor´s histogenic or cytogenic origin 1,27 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above benefits that obtain from the histopathological examination, it also provides useful data for epidemiological studies about cancer in any region of the world 27 . The recent results of cancer incidence in only one city (Karbala) in Iraq showed that the GIT organs developed the most common cancers over all periods of study.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Comoretto et al demonstrated that the combined use of MRI and FDG PET-CT had a greater diagnostic accuracy for detecting residual or recurrent disease compared to either modality individually [25]. In addition, PET is reportedly useful for differentiating recurrent NPC tumors from post-radiation changes, such as tissue necrosis, fibrosis and edema [23,[26][27][28][29]. However, in the early postradiation period, FDG uptake can be elevated secondary to inflammation following radiotherapy.…”
Section: Role Of Imagingmentioning
confidence: 99%
“…5 However, conventional endoscopy has limitation in detecting superficial lesion that makes unnecessary biopsy often happen. 6,7 Narrow Band Imaging is an endoscope technique that uses narrow-band spectrum as a filter to increase the visualization of vascular pattern. Narrow Band Imaging can detect superficial lesion, so that unnecessary biopsy can be reduced.…”
Section: Introductionmentioning
confidence: 99%